Regulation of biofilm formation in Klebsiella pneumoniae - Li, Yin; Ni, Ming (Frontiers in Microbiology, 2023)
Klebsiella pneumoniae is an important gramGram-negative opportunistic pathogen that is, which is responsible for a variety of nosocomial and community-acquired infections.K. pneumoniae has become a major public health issue due owing to the rapid global spread of extensively-drug resistant (XDR) and hypervirulent strains. Biofilm formation is an important virulence trait for of K. pneumoniae. A Bbiofilm is an aggregate of microorganisms attached to an inert or living surface by a self-produced exo-polymeric matrix whichthat includes proteins, polysaccharides and extracellular DNA.Biofilms are a type of polymerization which microorganisms attach to inert or active surface through the extracellular polymeric substances they produce. Bacteria within the biofilm are shielded from antibiotics treatments and host immune responseshost immune responses and antibiotics, making it more difficult to eradicate K. pneumoniae-induced infection. However, the detailed mechanisms of biofilm formation in K. pneumoniae are still not clear. Here, we focused reviewed on the factors involved in the biofilm formation of K. pneumoniae, which will might provide new clues for addressingto address this health clinical challenge.